A Pilot Trial Targeting the ICOS–ICOS‐L Pathway in Nonhuman Primate Kidney Transplantation. Issue 4 (20th February 2015) - Lo, D. J.; Anderson, D. J.; Song, M.; Leopardi, F.; Farris, A. B.; Strobert, E.; Chapin, S.; Devens, B.; Karrer, E.; Kirk, A. D.
Abstract: Costimulation blockade with the B7‐CD28 pathway‐specific agent belatacept is now used in clinical kidney transplantation, but its efficacy remains imperfect. Numerous alternate costimulatory pathways have been proposed as targets to synergize with belatacept, one of which being the inducible costimulator (ICOS)–ICOS ligand (ICOS‐L) pathway. Combined ICOS–ICOS‐L and CD28‐B7 blockade has been shown to prevent rejection in mice, but has not been studied in primates. We therefore tested a novel ICOS‐Ig human Fc‐fusion protein in a nonhuman primate (NHP) kidney transplant model alone and in combination with belatacept. ICOS‐Ig did not prolong rejection‐free survival as a monotherapy or in combination with belatacept. In ICOS‐Ig alone treated animals, most graft‐infiltrating CD4 + and CD8 + T cells expressed ICOS, and ICOS + T cells were present in peripheral blood to a lesser degree. Adding belatacept reduced the proportion of graft‐infiltrating ICOS + T cells and virtually eliminated their presence in peripheral blood. Graft‐infiltrating T cells in belatacept‐resistant rejection were primarily CD8 + CD28 −, but importantly, very few CD8 + CD28 − T cells expressed ICOS. We conclude that ICOS‐Ig, alone or combined with belatacept, does not prolong renal allograft survival in NHPs. This may relate to selective loss of ICOS with CD28 loss. Abstract : This study demonstrates that blockade of the ICOS–ICOS‐Ligand pathway, when used as monotherapy or paired with CD28‐B7 blockade, does not prolong renal allograft survival in a nonhuman primate kidney transplant model.